On the aspects of low voltage direct current electric systems of all electric ships - Zhang, Xinan (2014)
In recent years, all electric ships (AESs) become increasingly popular due to their high efficiency, flexibility and reliability. Many research papers are published to improve the stability and capability of AES power systems. Generally, DC electric distribution is employed on-board to support most of the electric loads, including tightly regulated power electronic loads and rapidly-varying loads. As acknowledged, the tightly regulated power electronic loads and rapidly-varying loads are nonlinear and can generate destabilizing effects on power systems in both small-signal and large-signal senses. Moreover, the share of such loads in modern electric systems, such as AES power systems, is on the rise. Therefore, the stability of AES power systems with the afore-mentioned nonlinear loads has to be studied.